2011
DOI: 10.1248/bpb.34.295
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of Gene Expression and Production of Promatrix Metalloproteinase 2 by Propionibacterium acnes-Derived Factors in Hamster Sebocytes and Dermal Fibroblasts: A Possible Mechanism for Acne Scarring

Abstract: Aberrant extracellular matrix (ECM) remodeling in sebaceous glands and pilosebaceous units in the skin is associated with scar formation under acne conditions. To investigate the involvement of Propionibacterium acnes (P. acnes), a Gram-positive anaerobic microbial species, in ECM remodeling in sebaceous glands and pilosebaceous units, we examined the effects of P. acnes culture media, formalin-fixed P. acnes, and peptidoglycan (PGN) from Gram-positive bacteria walls on the production of promatrix metalloprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 27 publications
0
25
0
4
Order By: Relevance
“…The aggravation of acne is likely to result in a disfiguring and permanent scar formation that carries a psychological and social impact on the patient's quality of life (8,30,31). Allen and LoPresti (32) reported the involvement of sunlight in the aggravation of acne vulgaris, and the current results indicated that triptolide inhibits UVB-enhanced sebaceous TG production in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 49%
“…The aggravation of acne is likely to result in a disfiguring and permanent scar formation that carries a psychological and social impact on the patient's quality of life (8,30,31). Allen and LoPresti (32) reported the involvement of sunlight in the aggravation of acne vulgaris, and the current results indicated that triptolide inhibits UVB-enhanced sebaceous TG production in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 49%
“…In addition, P. acnes has been reported to augment the expression of pro‐MMP‐1/procollagenase‐1 and pro‐MMP‐9/progelatinase B in human monocytes, 8 and that of pro‐MMP‐2/progelatinase A in human dermal fibroblasts 9 . We have also reported that P. acnes and PGN augment the expression of pro‐MMP‐2 in hamster sebocytes 16 …”
Section: Introductionmentioning
confidence: 52%
“…Hamster sebocytes were cultured in DMEM /F12 supplemented with 6% heat‐denatured fetal bovine serum (JRH Bioscience, Tokyo, Japan), 2% human serum (ICN Biochemicals, Costa Mesa, CA, USA), 0.68 mmol/L l ‐glutamine (Invitrogen, Carlsbad, CA, USA), and recombinant human epidermal growth factor (10 nmol/L) (Progen Biotechnik GmbH, Heidelberg, Germany) as previously described 22 . For PGE 2 and pro‐MMP‐2 production, the cells were treated for 24 h with NDFX (10–50 μg/mL) (kindly provided by Otsuka Pharmaceutical Co., Tokyo, Japan) or CLDM hydrochloride (10–50 μg/mL) (AppliChem GmbH, Darmstadt, Germany) in the presence or absence of PGN (5–50 μg/mL) from Staphylococcus aureus (Sigma Chemical, St Louis, MO, USA) in Dulbecco’s modified Eagle’s medium (DMEM)/F12 supplemented with 0.2% lactalbumin hydrolysate (Sigma Chemical, St Louis, MO, USA) 16,24 . In this series of experiments, hamster sebocytes were used as far as the third passage level.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that antimicrobial activity of ascorbic acid derivatives on bacterium differs by its species and strains 27. The Gram-positive bacterium S. aureus and Gram-negative bacterium E. coli exist as resident microflora on human skin and are associated with acne development in concert with P. acnes 1012. Therefore, zinc ascorbate may sufficiently inhibit the growth of S. aureus and E. coli , which participate in acne development in the concentration that is lower than other ascorbic acid derivatives and zinc, similar to its effect on P. acnes 13.…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus and E. coli exist in the skin lesions of acne patients; they are associated with acne development in concert with P. acnes 1012. We recently reported that the ascorbic acid derivative zinc ascorbate inhibits the growth of P. acnes in vitro, and it may provide novel insights into acne therapy 13.…”
Section: Introductionmentioning
confidence: 99%